Analysis of Exchange Rate Hedging Decisions and Sales Growth on the Financial Performance and Financial Stability of Imports and Exports in Indonesia from 2022 – 2024 - Ningsi Rutiana Simatupang; Nur Anita (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the effect of exchange rate hedging decisions and sales growth on financial performance and financial stability. The independent variables in this study are exchange rate hedging and sales growth. The dependent variables in this study are financial performance and financial stability. The population in this study consists of all import-export companies in Indonesia listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. The research period was conducted over 3 years. This study used a quantitative method with a sample of 50 companies, resulting in a sample of 150 based on certain criteria. The research analysis method used multiple linear regression with the help of SPSS 27. The results showed that exchange rate hedging had a positive effect on improving financial performance and financial stability. Meanwhile, sales growth and revenue growth together have a positive and significant effect on financial performance and financial stability. The results of this study are expected to contribute theoretically to the literature on financial management and risk management, as well as provide practical benefits as consideration for hedging policies for the financial management of import-export companies.